Factors Affecting the Realization of MSME Financing at Sharia Bankaltimtara Samarinda - Iswanto, Bambang; Ain Fitriah, Rinna Ramadhan; AF, Muh Shadiqul Fajri; Munir, Misbahul (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2022)
This research was motivated by the importance of financing the MSME sector based on sharia principles to overcome the problem of limited MSME business capital and avoid the element of usury. The research aims to determine what factors had a significant effect on the realization of MSME financing at the Sharia Bankaltimtara, Samarinda. To analyze the factors that influenced the realization of MSME financing, the method used was multiple linear regression analysis. Based on the results of the regression coefficient test, there are two factors that have a significant influence on the realization of MSME financing at Sharia Bankaltimtara Samarinda, namely the customer's net profit per month and the value of the financing collateral. Meanwhile, other factors such as education level, length of business, type of business, composition of business capital, and type of financing contract did not significantly affect the realization of financing in the MSME sector. The implication of this research is as an evaluation for Bankaltimtara Syariah Samarinda that increasing MSME financing must focus on assessing customers' monthly net profit and the value of financing collateral.